Peningkatan Hasil Belajar Writing Melalui ‘Mega De Shop’ Siswa Kelas VII E Semester Ganjil Tahun Pelajaran 2017 / 2018 di Smp Negeri 2 Trenggalek - Dwi Margani Sa’adah (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
Writing is a type of skill of putting words to be a sentence which then becomes a paragraph which contains the main idea. This class  Action Research is aimed at improving students' learning outcomes in the writing of students of class VII E SMP Negeri 2 Trenggalek. From the results of previous writing tests obtained data that only 46% of students who got score above KKM. This is caused by various things, namely; they are less able to explore topics, ideas are less clear, not well ordered sentences and some errors in the use of vocabulary, grammar and spelling. Another problem faced is the low motivation of learners in doing the task of writing. Likewise learning activities also less varied. Knowing that how important this writing skill is, this problem needs to be solved immediately. Mega De Shop is a learning technique that can facilitate learners to be more active in finding vocabulary as a basic writing because Mega De Shop is a technique by using the image media combined with the learning steps of Two Stay Two Stray model which has been modified. So by using this technique can improve student learning outcomes. The issues that are important to know related with this research is we formulated as follows: "How to improve the results of learning writing through" Mega De Shop "in class VII E students of odd semester 2017/2018 school year at SMPN 2 Trenggalek? To solve the existing problem, researchers used "Mega De Shop" in learning. This research is a Classroom Action Research consisting of 4 stages of 2 cycles. From the action done on cycles 1 and 2 obtained good results because there is an increase in the ability of students of SMP Negeri 2 Trenggalek in writing as it is known from the condition before the research that is 14 students or exactly 47%, in cycle 1 then up 20% to 67% ie 20 students. In cycle 2 it rises 24% to 90% or 27 students who reach KKM. Based on the results obtained from analyzing the data sources used, we can conclude that Classroom Action Research through "Mega De Shop" can improve students' ability in writing skill in grade VII E students of SMP Negeri 2 Trenggalek. This can be inferred from the increase in the number of students who achieve the minimum mastery criteria in the class.